2017
DOI: 10.19044/esj.2017.v13n29p172
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Factors Affecting Teachers’ Use of Short Stories in the Teaching of Kiswahili Grammar in Secondary Schools in Nandi North Sub-County, Kenya

Abstract: This study investigated attitude factors affecting teachers' use of short stories in the teaching of Kiswahili grammar in Secondary Schools in Nandi North Sub County, Kenya. The design for this study was descriptive survey. The total target study population was 50 Kiswahili language teachers in Secondary Schools in Nandi North Sub-County, in Kenya. Sampling was done through stratified and simple random sampling techniques to arrive at 50% of the target population. A total of 15 Kiswahili language teachers (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Short stories are also a good context for teaching grammar. For example, Lihanda and Agufana (2017) found that although few of their sample of teachers used short stories to teach Kiswahili grammar, the teachers had a positive attitude towards their use, and the study recommended that teachers should use them for effective Kiswahili grammar teaching. The culture load found in storytelling can be regarded as another advantage of using short stories.…”
Section: Benefits Of Short Storiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Short stories are also a good context for teaching grammar. For example, Lihanda and Agufana (2017) found that although few of their sample of teachers used short stories to teach Kiswahili grammar, the teachers had a positive attitude towards their use, and the study recommended that teachers should use them for effective Kiswahili grammar teaching. The culture load found in storytelling can be regarded as another advantage of using short stories.…”
Section: Benefits Of Short Storiesmentioning
confidence: 99%
“…In terms of learning vocabulary, the findings of Dolma and Boonprasitt (2016) supported the results above in the sense that the use of the self-collection vocabulary strategy in short story reading significantly enhanced the vocabulary of seventh grade Bhutanese students. As well as vocabulary, stories are also known to enhance grammar study (Lihanda & Agufana, 2017) and reading comprehension and, therefore, they should be given preference in teaching (Al-Dersi, 2013). Table 2 shows the responses to the five items measuring their visit to the library and buying and exchanging stories.…”
Section: Findings On the First Dimensionmentioning
confidence: 99%